Hubungan Perolehan Nilai Ujian Nasional Fisika Pada Tahun Pelajaran 2011/2012 (Studi Kasus Di SMA Negeri 39 Jakarta Timur) - Alis, Ratih Wulansari (Jurnal Gemaedu, 2018)
This study aims to determine whether there is a relationship between the acquisition of the value of try out with the value of National Examination physics in the academic year 2011/2012 (case study in SMA Negeri 39 East Jakarta). The hypothesis proposed in this study is "there is a relationship between the acquisition of the value of try out with the value of National Examination physics in the academic year 2011/2012 (case study in SMA Negeri 39 Jakarta Timur)". This research was conducted at SMA Negeri 39 Jakarta Timur in academic year 2011/2012. The sample was taken by simple random sampling by taking 6 classes ie XII IPA 1 to XII IPA 6 with a sample of 15 students in each class. This research uses the ex-post facto method with the correlation technique. Obtaining try out (X) data by using try out test made in school, MGMP level studio, MKKS of East Jakarta, and made by DKI Jakarta province and physics exam in academic year 2011/2012 (Y) using National Examination test of physics, both instruments are multiple choice questions with 5 answer choices (A, B, C, D, E). The analysis result for Normality Test using error estimation yield = = 0,981> 0,093 concluded data not normally distributed. Obtaining data to try out data with an average of 5.70 was correlated with National Examination physics with an average of 8.65. Result = 15,05> 3,95 = for significance level a = 0,05 and Fhitung = 15,05> 6,90 = Flabci for significance level a = 0,01 concluded significant linear regression model. Furthermore = 1.47 <1.65 = at the significance level a = 0.05 and = 1.47 <2.03 = Ftable at the level of significance a = 0.01 concluded linear regression. Test of significance of correlation at significance level a = 0,05, = 3,85> 1,99 = and significance level a = 0,01, = 3,85> 2,65 = coefficient of determination equal to 14,44%. It was concluded that the acquisition of small try out value did not contribute to the national physics examination value that was maximal compared to the try out value.